The Tyranny of Outcomes. Issue 3 (3rd June 2021) - Clapton, Gary
Abstract : This perspective piece highlights an everyday feature of the work of UK social workers, their managers and policy-makers. The use of outcomes as a measurement of achievement. The growth of the use of outcomes, their present-day ubiquity, the professed efficacy of their use and their connections with managerialism are then problematised. It is suggested that the deployment of outcomes can serve as a seeming assurance of efficiency. This is to the detriment of less technocratic, softer, more uncertain, yet more realistic and humanist, efforts to describe change and growth. No solutions – or outcomes – are offered. Rather this short perspective piece adopts the approach of 'a problem well stated is a problem half-solved'.